Activation of Minilateral Alliances with the Participation of European Countries and Ukraine in the Context of Russia’s Armed Aggression: Security Dimension - Teresa Astramowicz-Leyk; Yaryna Turchyn; Olha Ivasechko; Oleh Tsebenko (Studia Warmińskie)
The article is devoted to the analysis of the activities of minilateral alliances, the member states of which are Ukraine and European countries seen through the prism of the security dimension. The definition of minilateralism, the origins of the concept, its strengths and weaknesses are presented. The authors focused on the importance and priorities of mini-alliance cooperation, in particular, the security dimension of Ukraine's cooperation within such alliances as: "The Lublin Triangle", "Associated Trio", "Quadriga", Tripartite Alliance, The Romania-Republic of Moldova-Ukraine Alliance, the Great Britain-Poland-Ukraine Alliance. The criteria of political, economic, military, and sanctions support of Ukraine by the countries-participants of minilateral alliances during the war are presented. The key challenges to the functioning of alliances and promising areas for further cooperation are highlighted. The authors used systemic, institutional, comparative and statistical methods, as well as method of document analysis and case study, to characterize the process of current activation of minilateral alliances within the Ukraine-European countries framework. The research paper summarizes the positive consequences of Ukraine’s minilateral cooperation with European countries, which contribute to overcoming modern security challenges.